KONTESTASI ENERGI ANTARA MASYARAKAT DESA RANTAU SAKTI DAN PLN DALAM PEMANFAATAN TENAGA LISTRIK DI DESA RANTAU SAKTI, KABUPATEN ROKAN HULU - Geovani Meiwanda (NATAPRAJA, 2018)
Desa Mandiri Energi is a program launched by the Central Government through the Ministry of Energy and Mineral Resources, and this program requires active roles from community in its implementation. The village of Rantau Sakti, one of the villages in Tambusai Utara Sub-district, is a village where the successful implementation of Mandiri Energi Village and formed PLT-Biogas Rantau Sakti. Biogas flow was obtained from the waste of Palm Oil which eventually able to become electrical energy for the community in some villages. The running and development of the Desa Mandiri Energi program was in line with the conflict with PLN Rayon Bagan Batu which was adjacent to North Tambusai District. This article will analyze in depth, like a coin that has two sides. On one hand, when the Mandiri Energi program in several places in Indonesia failed, the program succeeded in North Tambusai Sub-district although it proved to be a conflict with PLN. Conflict goes without mediation between the two actors with different perceptions, which indicates the absence of government in the conflict management process.